Morphofunctional Features of the Face: Interrelation of Bone Structure, Soft Tissues, and Subjective Aesthetic Evaluation - Doroshenko, О. М.; Bida, В. І.; Doroshenko, М. В.; Omelianenko, О. А.; Doroshenko, М. М. (Actual Dentistry, 2025)
Abstract. The human face is a central element of identity, playing a crucial role in social interaction, emotional expression, and self-perception. Its aesthetics are inextricably linked to the complex interplay between underlying bone structures and overlying soft tissues. This morphofunctional complex not only provides vital functions such as breathing, chewing, and speech but also forms a unique facial expression. While objective anatomical parameters play a significant role, subjective aesthetic evaluation is equally important, as cultural, individual, and psychological factors heavily influence the perception of beauty. A more in-depth analysis of these interactions will allow for a better understanding of the etiology of aesthetic disharmonies and the development of more effective and individualized approaches to their correction. Aim: to systematize current understanding of the morphological and functional features of the face by analyzing the interrelation between bone structures and soft tissues, and to investigate the influence of these interactions on the subjective aesthetic perception of attractiveness. Material and Methods. Information search and analysis of scientific sources were conducted using the scientometric databases Web of Science, PubMed, and Google Scholar over the last 15 years. Conclusion. Given the dynamic development of digital technologies and analytical methods, future research should focus on further integrating multifactorial models of facial analysis. This includes not only an accurate assessment of bone structures and soft tissue profiles but also consideration of the patient’s psychoemotional state, sociocultural perceptions of beauty, and individual motivation for treatment.